Unexpected hydrophobicity on self-assembled monolayers terminated with two hydrophilic hydroxyl groups. Issue 46 (23rd November 2021) - Mao, Dangxin; Wang, Xian; Wu, Yuanyan; Gu, Zonglin; Wang, Chunlei; Tu, Yusong
Abstract : An unexpected hydrophobicity with a contact angle of 82° on (OH)2 -SAM terminated only with two hydrophilic OH groups was found, which is attributed to the formation of a hexagonal-ice-like H-bonding structure in the OH matrix of (OH)2 -SAM. Abstract : Current major approaches to access surface hydrophobicity include directly introducing hydrophobic nonpolar groups/molecules onto the surface or elaborately fabricating surface roughness. Here, for the first time, molecular dynamics simulations show an unexpected hydrophobicity with a contact angle of 82° on a flexible self-assembled monolayer terminated only with two hydrophilic OH groups ((OH)2 -SAM). This hydrophobicity, verified by a water slip phenomenon characterizing the friction on the (OH)2 -SAM surface, is attributed to the formation of a hexagonal-ice-like H-bonding structure in the OH matrix of (OH)2 -SAM, which sharply reduces the hydrogen bonds between the surface and the water molecules above. The unique simple interface presented here offers a significant molecular-level platform for examining the bio-interfacial interactions ranging from biomolecule binding to cell adhesion.